Integrasi Nilai Keislaman Sebagai Strategi Epistemologis Dalam Membentuk Berpikir Kritis Siswa di Era Post-Truth: Studi di SMA Muhammadiyah 1 Klaten - Shofia Fadila Nur Husna; Muhammad Wildan Shohib (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The post-truth era is characterized by the weakening authority of facts and the strengthening of emotional opinions. In this situation, Islamic education faces challenges not only in the moral domain, but also in the epistemological domain concerning how students distinguish truth from falsehood. This study aims to examine the integration of Islamic values focused on sidq, tabayyun, and *tafakkur as an epistemological strategy in shaping students’ critical thinking in senior high school using a qualitative method with a case study approach. This research was conducted at SMA Muhammadiyah 1 Klaten. Data were collected through in-depth interviews with 2 teachers, 1 vice principal for curriculum, and 5 grade 12 students (selected based on students who had completed the entire series of Islamic Religious Education learning and possessed a more mature level of thinking), classroom observations, and critical-thinking task simulations. The results of this study demonstrate that Islamic values have not yet been explicitly utilized as tools for epistemological verification. This article offers a conceptual framework to bridge Islamic values and critical-thinking skills in the era of disinformation.